Deradicalization of Religion Through Pluralism Education Methods in Jembrana Bali - Made Saihu (Jurnal Pendidikan Islam, 2020)
Deradicalization through education is one of the main agendas in counteracting the massive spread of radicalism in Indonesia. This study aims to describe the effectiveness of the religious pluralism education method from the perspective of "Allison Cumming-McCann" at SMPN 4 and SMAN 1 Negara Jembrana to implement deradicalization. This study uses a qualitative method with the type of case study (multiple cases). Data were obtained through observation and unstructured interviews. This study's results indicate that the optimization of several religious pluralism education methods of "Allison Cumming-McCann" is in the form of contribution, enrichment, and decision-making & social action methods. Even though Muslims' position in the two educational institutions is a minority, this optimization is expected to strengthen harmonious relations between students of different religions and cultures. To a certain extent, there is also active involvement between students to prepare for each religious ceremony. This study provides an example of a pluralism educational model in a multicultural environment in the deradicalization effort through education.